EXPLORING THE IMPACT OF DEVELOPMENT TALENT, SALARY AND REWARD, THE EFFECT OF MANAGERS, AND ORGANIZATIONAL STRUCTURE ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE" IN RWANDA TELECOMMUNICATIONS INDUSTRY: A CASE OF MTN RWANDA (Mobile Telephone Network) - Leandre Mushinzimana; Angela Teressia; Sapta Dwikardana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
In recent years, the issue of employee performance has become crucially important to the development and achievement of organizational goals and objectives. This study investigates the elements influencing job satisfaction to enhance employee performance at MTN Rwanda and establishes relationships between the independent variable, mediator variable (job satisfaction), and supportive employee performance. The primary tool for collecting data for this study will be questionnaires. We will review theoretical and empirical studies to identify the variables that could affect employee performance. Purposive sampling involved 198 selecting from (subordinate, lower management, middle management and senior management). The study will employ quantitative methodology to analyze the variables using the SMART PLS software. The findings of this research are several. First, salary and reward have a positive and significant influence on employee performance in Rwanda's telecommunications industry. Second, the development of talent has no significant effect on employee performance. Third, the impact of managers has no significant effect on employee performance. Fourth, organizational structure has a positive and important influence on employee performance. Sixth, job satisfaction does mediate the relationship between (the development of talent, salary and reward, the effect of managers and organization structure) and employee performance.